Strong hypoxia reduces leptin synthesis in purified primary human trophoblasts. Issue 4 (April 2015) - Nüsken, E.; Herrmann, Y.; Wohlfarth, M.; Goecke, T.W.; Appel, S.; Schneider, H.; Dötsch, J.; Nüsken, K.D.
Abstract Introduction Oxygen availability severely affects placental function. During placental hypoxia, stabilization of hypoxia inducible factors (HIFs) affects transcription, and leptin gene expression concomitantly increases in vivo and in vitro. However, a causal relationship is uncertain. Methods We investigated the effect of oxygen availability on HIF-1 alpha (HIF1A) and leptin regulation in primary human trophoblasts isolated from six normal term placentae cultured at 0.1%, 1%, 3%, and 8% oxygen for 6 h, 24 h and 48 h. Gene expressions of leptin (LEP), leptin receptors (LEPR), HIF1A, insulin receptor (INSR) and further genes relevant in hypoxia (VEGFA, EPO, NOS2) or apoptosis (BCL2, BAX, Tp53) were examined. Leptin, HIF1A, INSR, phospho-AKT/AKT (insulin receptor signaling), caspase 3 and cleaved caspase 3 (apoptosis) proteins were measured. Results A hypoxic reaction with stabilization of HIF1A protein as well as up-regulation of HIF1A and VEGFA gene expressions, but without any hint for apoptosis, was present at 0.1% and 1% oxygen. However, leptin protein concentration (cell supernatants) peaked at 8% oxygen (normoxia) and was significantly reduced at 0.1% oxygen. There was no significant correlation between leptin and HIF1A, neither on the gene nor on the protein level. Discussion Elevated leptin gene expression in hypoxic placentas may not originate from trophoblasts, but from other placental cells, or from interaction of trophoblasts with other cells. Not only fetal hyperleptinemia, but also fetal hypoleptinemia under hypoxic conditions is conceivable. Strategies to prevent leptin dysregulation during pregnancy should be elucidated to protect the offspring from fetal programming of leptin resistance and adiposity in later life.